TEXCT COMPLEXITY: THE LAST VICTIM OF THE WAR (STORY) BY OTKIR HOSHIMOV - Erkinova Muqaddas Olim qizi; Jo‘rayev Muhammadrahimxon Murod o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Text complexity constitutes a multidimensional construct that encapsulates the intricate interplay between linguistic, cognitive, and conceptual elements within written discourse. It extends beyond mere lexical difficulty, encompassing syntactic sophistication, discourse cohesion, thematic profundity, and inferential demands placed upon the reader. Accurate assessment of text complexity necessitates an integrative approach combining quantitative metrics, such as readability indices and corpus-based analyses, with qualitative evaluations that consider narrative structure, genre-specific conventions, and conceptual abstraction. Moreover, comprehension is profoundly mediated by reader-intrinsic factors, including prior knowledge, metacognitive strategies, and motivational orientation. A nuanced understanding of text complexity is pivotal for optimizing pedagogical practices, facilitating differentiated instruction, and promoting higher-order literacy skills, thereby fostering critical engagement with complex texts across diverse educational contexts.